Healthy Internet Counseling About the Dangers of Hoax in the Covid-19 Pandemic Period for Students SMK Darut Taqwa Sengonagung Purwosari Pasuruan: Penyuluhan Internet Sehat Tentang Bahaya Hoax di Masa Pandemi Covid-19 Bagi Pelajar SMK Darut Taqwa Sengonagung Purwosari Pasuruan - Rosadi, Muhammad Imron; Misbach Munir; Mochamad Hasyim (LPPM Universitas Yudharta Pasuruan, 2022)
that can be obtained by using the internet. The issue of hoaxes during the Covid-19 pandemic is very high through internet and social media networks. Negative opinions, slander, hate spreaders that are accepted and attack parties or make people afraid, threatened and can harm the reported party so that it can damage reputation and cause material losses. This activity aims to make Darut Taqwa Vocational School students not easily swayed by HOAX news, understand how to reject HOAX, surf the internet healthily, be wise in social media, as an antidote to hoaxes, and provide education to friends, relatives, family, and the general public about the dangers. Hoax. The method used in this service is the preparation stage, the implementation stage, namely seminars and workshops, monitoring and evaluation stages. The results of this community service activity include: increasing students' insight into healthy and safe internet use and avoiding hoax sites and news; Increased knowledge of students in the use of social media to digest and share hoax and fact information.